Buddhist ethics and the Bodhisattva path Śāntideva on virtue and well-being - Harris, Stephen E. (Bloomsbury introductions to world philosophies., 2024)
"Santideva's 8th century Mahayana Buddhist classic, the Guide to the Practices of Awakening (Bodhicaryavatara), has been a source of philosophical inspiration in the Indian and Tibetan traditions for over a thousand years. Stephen Harris guides us through a philosophical exploration of Santideva's masterpiece, introducing us to his understanding of the compassionate bodhisattva, who vows to liberate the entire universe from suffering. Individual chapters provide studies of the bodhisattva virtues of generosity, patience, compassion, and wisdom, illustrating the role each plays in Santideva's account of well-being and moral development. Harris also provides in-depth analysis of many of Santideva's most influential arguments, demonstrating how he employs reasoning as a method to cultivate moral character. As the first book-length English language philosophical study of Santideva's most influential text, this will be essential reading for students and scholars of Buddhist ethics, as well as for anyone interested in intercultural ethics and the philosophy of well-being" -- Publisher's website.